Disparities in Kidney Disease: The Need for Targeted Programmes and Interventions to Promote Health Equity across the Globe: Disparities in Kidney Disease - Okoro, Roland; Aluh, Deborah (Pakistan Journal of Kidney Diseases, 2024)
Kidney disease is a major public health issue that affects over 850 million people globally. The burden of kidney disease varies greatly around the world, as do its identification and treatment. The causes of these disparities are multifactorial, including socioeconomic status, race and ethnicity, sex/gender, age, geographic location, language and cultural barriers, healthcare system and provider factors, and social determinants of health, among others. In this paper, poor health outcomes associated with disparities in kidney disease, strategies to mitigate these disparities, and the importance of diversity, equity, and inclusion (DEI) in kidney disease are highlighted, while targeted programmes, and interventions rooted in DEI tenets are recommended.